Chankyas Neeti: Political Ethics and Strategies: Exploring Chanakya's Vision for India's Political and Economic Transformation (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Chanakya imagined India as a country which would put itself as the trailblazer – politically, monetarily and socially. His perfect work of art, Arthashatra, portrays from various perspectives the India he had always wanted. When he composed this volume of epic extent, the nation was ridden in feudalism and shut and independent economy. The economy in view of indigenous methods for generation was in a transitional stage, moving towards the propelled parts of dissemination and creation. Culture and provincial legislative issues coordinated the manner by which exchange was finished.